Regeneration of the achilles tendon in rats using platelet-rich plasma and corticosteroids - Kasatka, Oleg; Ashukina, Nataliya; Ivanov, Gennadiy; Petrenko, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Achilles tenopathy is one of the common diseases of the lower limb in sportsmen. Prevalence of achilles tendopathy is 60 % out of all such pathologies occurring in the foot area. In most cases, the treatment of this condition is conservative, using the methods of physical rehabilitation, as well as non-steroidal anti-inflammatory drugs. Objective: to study the peculiarities of the regeneration of the achilles tendon in rats after its traumatic injury under conditions of local use of corticosteroids and xenogenic platelet-rich plasma. Methods: surgical simulated an achilles tendon injury cutting of ⅓ of its width according to the arthrotomy type in 24 laboratory rats weighing 300–350 g. After the operation, the animals were randomly divided into three groups: without treatment in the postoperative period —1st (control), betamethasone injection on the 3rd day after the operation and then every 7th d ay — 2 nd g roup a nd p latelet-rich p lasma injection — 3rd g roup. T he a nimals w ere s acrificed o ne week after the 3rd and 4th injections of the preparations, the controls on the 31st and 38th days after the operation. The material was investigated by histology with the analysis of collagen in polarized light. Results: in rats of all groups in the area of the achilles tendon defect on the 38th day after the injury, the formation of tendon-like tissue was established. In animals of the 2nd and 3rd groups, densely packed bundles of collagen fibers, built from type I collagen, were located in it. Type III collagen occupied small areas, it was larger in rats of the 2nd group. The control revealed signs of chronic inflammation and a maximum deviation from the structure of the normal tendon. Conclusions: the treatment of traumatic injury to the achilles tendon of rats by the local administration of corticosteroid and xenogenic platelet-rich plasma can prevent the development of inflammation and optimize the reparative process.